Spontaneous infarction of papillary thyroid carcinoma in sickle cell trait patient leading to missed diagnosis on fine-needle aspiration cytology - Vedita, M Bobde; Meena, A Pangarkar; Dinkar, T Kumbhalkar (Indian Journal of Case Reports, 2020)
Papillary thyroid carcinoma (PTC) is a common thyroid malignancy in adults and children. With classical microscopic features seen, fine-needle aspiration cytology (FNAC) is a cost-effective and less invasive procedure to diagnose thyroid lesions. Post- FNAC infarction is common in PTC and other solid benign and malignant lesions. Spontaneous infarctions in various organs are seen in sickle cell disease and trait patients in hypoxic conditions. Aspiration of only necrotic material and no distinct microscopic features cause problems in diagnosis. Infarction should be kept in mind while reporting aspirates from sickle cell patients.